The layers of the main street - Pecze, Anna (4D Journal of Landscape Architecture and Garden Art, 2018)
The subject of the paper is one of the most significant element of urban morphology – the street. Researching its identity, essence and morphology of small towns in the Great Plain makes the framework of the study.The research is based on the hypothesis that “the main street is the essence of the town”. It is not only the towns’ cultural imprint, but its soul, the concentration of central functions, shops and most of the hospitality can be found here.Owing to the complexity of this linear urban element, a few layers are defined that are presenting the structure, development, changes in the history and everyday life of the settlement.Furthermore, these layers enable to depict the fine methodological differences how the people perceive their surroundings.Defining the model that define certain characteristics of the Main Streets that make the readability possible is the fulcrum of this paper, which will contain characteristic examples, taken from the Ph.D. in progress of the author.
Keywords: Main Street; urban layers; urban sociology; small town; development of the settlemens